Evaluation of dietary intake and quality of life on risk of osteoporosis among adults in Universiti Malaysia Terengganu - Ang, Shiao Ying; Khairil Syazmin Kamaruddin,; Hayati Mohd Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The present study aimed to evaluate the link between dietary intake and quality of life on risk of osteoporosis among adults in Universiti Malaysia Terengganu. This study involved 73 respondents (61.6% students and 38.4% staff) aged 19 to 50 years old. The median BMI among respondents was 23.6 (6.08) kg/m2, categorized as normal weight. 58% of respondents had normal body weight, while 35.6% respondents were overweight/obese and 6.1% were underweight. Result revealed that serum calcium and phosphorus of respondents were 8.4 (0.65) mg/dL and 3.0 (0.70) mg/dL, respectively. Even though the median calcium intake of respondents was only 46.5% RNI (371.9 mg/day), the calcium concentration in serum achieved 98.8% at reference level. Moreover, 129.2% of phosphorus RDA intake (904.6 mg/day) resulted in 70% of respondents with serum phosphorus at reference level. A majority of calcium and phosphorus rich foods had low frequency consumption score among respondents. BMI and body fat percentage shows no relationship with serum calcium but have a weak reverse relationship with serum phosphorus (Ï: -0.215, p=0.07; Ï: -0.247, p=0.04). Additionally, Physical Health Composite Scale Score (PCS) and Mental Health Composite Scale Score (MCS) of respondents (53.86 (10.00); 52.42Â±7.44) were average and had a weak relationship with serum calcium (Ï: 0.237, p=0.04) but no relationship with serum phosphorus. Lastly, there was gender difference in terms of association between body fat percentage, BMI, quality of life, phosphorus intake and serum calcium and phosphorus.